Policy Implications for the Green Bank Development in the Context of Global Climate Change - Nga Phan Thi Hang (Emerging Science Journal, 2022)
With the global financial crisis in 2008, climate change, and the COVID-19 pandemic, most countries worldwide have re-thought their organization and operating models in their financial systems, including the banking system. In Vietnam, sustainable economic development has become an essential need in the long term. However, sustainable development requires a balance between economic growth and environmental protection. Therefore, Vietnam has chosen to develop a green economy, in which "green banks" have an essential role. Green banking is a future banking model that balances all stakeholders' economic and environmental benefits and costs in banking activities. Green banking emerges as an ideal model for future banking, a foundation for a green economy and sustainable development. Therefore, the article analyzes the current situation and some challenges to promoting the development of green banking in Vietnam and proposes policy recommendations to promote green banking development in Vietnam in the coming time. The article used methods to test the reliability of Cronbach's alpha scale, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and SEM to test the research hypotheses based on surveying 700 commercial bank managers and collecting data by a convenient sampling method from June 2021 to December 2021. Research novelty explores five factors affecting green bank development with a significance level of 1.0%. Finally, the author had policy implications for developing the green bank in the future. Doi: 10.28991/ESJ-2022-06-04-011 Full Text: PDF